2014
DOI: 10.1590/s0100-736x2014000100005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of Anaplasma marginale in cattle: quantitative evaluation of a real-time PCR (Polymerase Chain Reaction) based on msp5 gene

Abstract: Pesq. Vet. Bras. 34(1):29-33, janeiro 2014 29 RESUMO.-[Diagnóstico molecular de Anaplasma marginale em bovinos: avaliação quantitativa de uma PCR em tempo real baseada no gene msp5.] A riquétsia Anaplasma marginale é considerada o principal agente da anaplasmose bovina. Devido a não especificidade dos sinais clínicos, a confirmação da infecção nos animais depende de testes laboratoriais. Recentemente, métodos de diagnóstico molecular têm sido aplicados para detecção de A. marginale em bovinos. No entanto,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…marginale. This endemic stability for anaplasmosis was similarly reported in a previous study in Brazil (Bacanelli et al, 2014). Endemic stability is an epidemiological state, in which there is high haemoparasites-infected ticks but clinical disease is absent in the population (Jonsson et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…marginale. This endemic stability for anaplasmosis was similarly reported in a previous study in Brazil (Bacanelli et al, 2014). Endemic stability is an epidemiological state, in which there is high haemoparasites-infected ticks but clinical disease is absent in the population (Jonsson et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…Although conventional PCR has been shown to be useful to determine the presence of Babesia and Anaplasma (Figueroa et al, 1993;Martins et al, 2008;Bilgiç et al, 2013;El-Ashker et al, 2015), more recently, qPCR has revealed to be more sensitive than the first for the detection of protozoan parasites in cattle (Criado-Fornelio et al, 2009). For the detection of anaplasmosis, some of the TaqMan ® based qPCR methods involve the amplification of species-specific genes such as the major surface proteins (msp) genes (Carelli et al, 2007;Bacanelli et al, 2014), and six msp (msp 1a, 1b, 2, 3, 4, 5) with the potential to be used in diagnostic assays have been identified on A. marginale (Kocan et al, 2003). The msp1 gene complex (composed of msp1a and msp1b) has been shown to be a well-conserved gene in A. marginale (de la Fuente et al, 2001;Bowie et al, 2002), whose products act as adhesin during invasion of bovine erythrocytes (McGarey et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the comparative analysis of the snPCR result for msp5 gene among splenectomized animals, cattle presented a significantly higher average frequency of infection than buffaloes. Other studies also reported that buffaloes had lower values (Silva et al 2014a(Silva et al , 2014b compared to the observed in cattle (Bacanelli et al 2014). A splenectomized buffalo was positive only 60 days after inoculation.…”
Section: Discussionmentioning
confidence: 78%
“…Two hypotheses may support this. The first, the animals came into contact with native strains of A. marginale from the moment they went to pasture, which contributed to a greater detection in snPCR for msp5 gene, present in several Anaplasma species and used for serological and molecular screening studies (Torioni de Echaide et al 1998, Bacanelli et al 2014. The second, over time, the AmRio 2 strain increased the number of DNA copies in the circulatory current of the ruminants and, consequently, contributed to a higher sensitivity of the molecular examination and this can be supported by the fact that this time (pasture period) includes the period when rickettsemia increases (2 to 6 weeks after infection), in which levels of 10 9 or more bacteria per milliliter of blood can be verified by quantitative PCR (Futse et al 2003, Han et al 2010.…”
Section: Discussionmentioning
confidence: 99%